Civic-mindedness: an ethical-political construction - Luis María Cifuentes Pérez (ADIDE Federación, 2008)
Civic-mindedness -as we will tackle it here- clearly surpasses the concept of mere good upbringing, because we consider education for civic consciousness and citizenship from ethical, legal and political outlooks, which go far beyond rules of polite behaviour and good manners that have been produced in every historical period and inside every culture. The concept of citizenship and civic-mindedness which is developed here goes deeply into a different direction: in the education of citizens which should be self-conscious of their rights and duties, as well as free, critical, responsible, active participant in public affairs and in solidarity with others. All these features which define the concept of citizenship have been hatched in western history in a complex and twisted way that must be previously well-known to understand the present situation.